PENGARUH KINERJA KEUANGAN, GOOD CORPORATE GOVERNANCE DAN STRUKTUR ASET TERHADAP KEBIJAKAN HUTANG (STUDI PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ-45 DI BURSA EFEK INDONESIA) - Ira Novita; Lilis Ardin (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
This research aimed to examine the effect of financial performance, good corporate governance and asset structure on debt policy of LQ-45 companies which were listed on Indonesia Stock Exchange 2014-2018. The research was quantitave. While, the population was all LQ-45 companies which were listed on Indonesia Stock Exchange 2014-2018. Moreover, the data collection technique used purposive sampling, in which the sample was based on criteria given. In line with, there were 14 companies as sample. Furthermore, the data analysis technique used multiple regression with Statistical Product and Service Solution (SPSS). The research result concluded Return on Asset (ROA) had negative effect on debt policy. It meant, companies had prefer to internal funds for its companyoperation. On the other hand, Return on Equity (ROE) had positive effect on debt policy. In other words, companies had prefer funding from debt, since it was used to reduce misuse of funds by management. Meanwhile, managerial pwnership had negative effect on debt policy. It meant, the greater the shares owned by managers, the smaller the debt proportion of corporate funding. In contrast, institusional ownership had high authority in the company. In addition, the asset structure did not affect the debt policy since the company won’t guarantee its assets to obtain debt.